Menopausal Status at Diagnosis is a Prognostic Indicator in Patients who are Operated for Uterine Carcinosarcoma - Hatice Bölek; Merih Yalçıner; Serhat Sekmek; Furkan Ceylan; Orhun Akdoğan; Doğan Uncu; Ozan Yazıcı; Elif Berna Köksoy (Ankara Üniversitesi Tıp Fakültesi Mecmuas)
Objectives: Uterine carcinosarcoma is a rare type of uterine cancer, and due to its rarity, there is limited evidence for prognostic factors and treatment. The objective of this study is to assess the influence of histologic, clinical, and demographic characteristics on overall survival (OS) and recurrence-free survival (RFS). Materials and Methods: Patients who had diagnosis of uterine carcinosarcoma and followed by the medical oncology department of three hospitals from Türkiye between January 2013 and January 2023 were retrospectively evaluated. All patients had local disease and were surgically managed, and patients were excluded if they did not have primary surgical management. Results: The study included 62 women who were primarily treated with surgery and had a median age of 64.5 (interquartile range=14) years. Recurrence was observed in 26 patients (41.9%), with a median RFS of 11.63 months [95% confidence interval (CI): 1.99-21.26]. A shorter RFS was observed in patients with myometrial invasion [hazard ratio (HR) 2.48, 95% CI 1.04-5.93, p=0.04], while postmenopausal diagnosis was a predictor for longer RFS (HR 0.02, 95% CI 0.004-0.14, p<0.001). The median OS was 43.17 months. Postmenopausal diagnosis was associated with prolonged OS (HR 0.003, 95% CI 0-0.45, p<0.001). Conclusion: The results of our study show that being diagnosed before menopause is linked to a shorter RFS and OS in women with uterine carcinosarcoma who had surgery to treat local disease.